Duration of Antimicrobial Prophylaxis in Patients Undergoing Major Hepatectomy With Extrahepatic Bile Duct Resection: A Randomized Controlled Trial. Issue 1 (January 2018) - Sugawara, Gen; Yokoyama, Yukihiro; Ebata, Tomoki; Mizuno, Takashi; Yagi, Tetsuya; Ando, Masahiko; Nagino, Masato
Abstract : Objective: To evaluate the optimal duration of antimicrobial prophylaxis in patients undergoing "complicated"' major hepatectomy with extrahepatic bile duct resection. Background: To date, 4 randomized controlled trials (RCTs) have assessed the duration of antimicrobial prophylaxis after hepatectomy. However, all of these previous studies involved only "simple" hepatectomy without extrahepatic bile duct resection. Methods: Patients with suspected hilar obstruction scheduled to undergo complicated hepatectomy after biliary drainage were randomized to 2-day (antibiotic treatment on days 1 and 2) or 4-day (on days 1 to 4) groups. Antibiotics were selected based on preoperative bile culture. The primary endpoint was the incidence of postoperative infectious complications. Results: In total, 86 patients were included (43 patients in each arm) without between-group differences in baseline characteristics. Bile culture positivity was similar between the 2 groups. No significant between-group differences were observed in surgical variables. The incidence of any infectious complications was similar between the 2 groups (30.2% in the 2-day group and 32.6% in the 4-day group). The positive rate of systemic inflammatory response syndrome and the incidence of additional antibiotic use were almost identical between the 2 groups. According to Clavien-Dindo classification, grade 3a or higher complications occurred in 23 patients (53.5%) in the 2-day group and 29 patients (67.4%) in the 4-day group ( P = 0.186). Postoperative hospital stay was not different between the 2 groups. Conclusions: Two-day administration of antimicrobial prophylaxis is sufficient for patients undergoing hepatectomy with extrahepatic bile duct resection [Registration number: ID 000009800 (University Hospital Medical Information Network, http://www.umin.ac.jp )]. Abstract : Supplemental Digital Content is available in the text